PENGARUH INFLASI, NILAI TUKAR RUPIAH, SUKU BUNGA DAN SELF ASSESSMENT SYSTEM TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI DI KANTOR WILAYAH DIREKTORAT JENDRAL PAJAK JAWA TENGAH II - Junianto, Setiawan; Harimurti, Fadjar; Suharno, Suharno (Universitas Slamet Riyadi, 2020)
Value Added Tax (VAT) is a tax that is imposed on the consumption of goods and services in the customs area. The purpose of this study is to examine the effect of inflation, the rupiah exchange rate, interest rates and self assessment system on value added tax receipts. The population of this study is the inflation rate in Central Java, the exchange rate of the rupiah against one US Dollar based on the tax rate, Bank Indonesia reference interest rate, the number of VAT notification period and all VAT receipts in the Central Java Regional Tax Office II with monthly data for the 2015- 2019. The data analysis technique used is descriptive analysis, the classic assumption test and the coefficient of determination (R2). The results of the study concluded that inflation and interest rates did not significantly influence VAT revenue, while the rupiah exchange rate and self assessment system had a significant positive effect on VAT revenue.